Neutral point clamped quasi Z source inverter for photovoltaic systems - M. Aravindan; V. Balaji; V. Saravanan; M. Arumugam (International Journal of Applied Power Engineering (IJAPE), 2019)
Multilevel inverters are becoming popular for power conversion in renewable energy systems, AC-DC hybrid micro grids etc. The voltage stress and inrush current through these inverter leg switches are quite higher as compared to the load ratings which increase the chances of inverter leg switch failure. A three level neutral point clamped quasi Z source inverter topology is discussed in this paper which has the features of lower component count, reduced capacitor voltage stress, and it can be operated at different control strategies to achieve wide range of voltage boosting ability, suited for photovoltaic (PV) systems. It also ensures continuous input current irrespective of the DC supply voltage variations and injects stable and smooth power to the load/grid. The effectiveness of the proposed inverter is verified by simulation results in MATLAB Simulink model as well as performing experiment with the help of a laboratory prototype.